The effect of sintering temperature on silica derived from rice husk ash - Nickel Oxide (SiO 2 -NiO) foam fabrication via slurry technique - Muda, Rizamarhaiza; Ahmad, Sufizar; Abd. Rahman, Hamimah; Taib, H. (IOP Publishing, 2018)
Fabrication of ceramic foam has been an interesting study in the field of a porous material due to the excellent mechanical and physical properties. This study presents an approach for the fabrication of Silica (SiO2) derived from rice husk ash (RHA) and Nickel Oxide (NiO) foams using the slurry technique, highlighting the sintering temperature affects. Polyvinyl alcohol (PVA) was used as binder and Polyurethane (PU) foam was applied as the space holder. The composition of SiO2 applied in this study was 20wt%. The PU foams dipped into SiO2-NiO slurry were dried and further sintered at three different sintering temperatures of 1050˚C, 1150˚C and 1250˚C. The morphologies of SiO2-NiO foams were observed by using the Scanning Electron Microscopy (SEM) and physical properties were determined by using Archimedes method for investigating the total porosity and bulk density. The identification of phases of SiO2-NiO foams were analysed by using X-Ray Diffraction (XRD). The XRD analyses indicated that there were only SiO2 and NiO present and no additional phases detected after sintering which implied the compatibility of SiO2 derived from RHA and NiO even temperatures up to 1250˚C. The density values of the SiO2-NiO foams were found to increase with increasing of sintering temperature. The densities were found to be in the range 0.5239g/cm³ to 0.6210g/cm3 and the percentage of the foams porosity were in the range of 69.71% to 75.19% .Thus it is concluded that the slurry technique is found to be successful to fabricate the SiO2 as derived from RHA and NiO foams. The sintering temperatures was found to affect the SiO2-NiO foams in turns of the density and porosity of the foam.